Estimation of the physico-chemical parameters of materials based on rare earth elements with the application of computational model; IOP Conference Series: Materials Science and Engineering; Vol. 112 : Fundamental Aspects of Rare-earth Elements Mining and Separation and Modern Materials Engineering (REES-2015) - Mamaev K. (2016, 2016)
Title screen